Novel Trends in Electrochemical Biosensors for Early Diagnosis of Alzheimer’s Disease - Pavla Valkova; Miroslav Pohanka (International Journal of Analytical Chemistry)
Background. Alzheimer’s disease (AD) is a multifactorial progressive and irreversible neurodegenerative disorder affecting mainly the population over 65 years of age. It is becoming a global health and socioeconomic problem, and the current number of patients reaching 30–50 million people will be three times higher over the next thirty years. Objective. Late diagnosis caused by decades of the asymptomatic phase and invasive and cost-demanding diagnosis are problems that make the whole situation worse. Electrochemical biosensors could be the right tool for less invasive and inexpensive early diagnosis helping to reduce spend sources— both money and time. Method. This review is a survey of the latest advances in the design of electrochemical biosensors for the early diagnosis of Alzheimer’s disease. Biosensors are divided according to target biomarkers. Conclusion. Standard laboratory methodology could be improved by analyzing a combination of currently estimated markers along with neurotransmitters and genetic markers from blood samples, which make the test for AD diagnosis available to the wide public.